Analysis of Purchases, Receivables and Cash Flow on Profit Through a Cost Saving System as an Intervening Variable at PT. Kalam Leverage Mulia - Wigy Prayoga; Supardi Supardi; Wisnu Panggah Setiyono (International Journal of Economics Development Research (IJEDR), 2023)
This research  aims to find out the results regarding  the analysis of purchases,  receivables and cash flow on profits through a cost savings system as an influencing variable for PT. Kalam noble leverage. This research   uses  quantitative  methods.  This method  is usually  carried  out  randomly,  uses  research  instruments, and applies data or statistical analysis to test predetermined hypotheses. In this context, a quantitative approach  is used by collecting data regarding  purchases of project materials,  receivables and cash flows during the 2018-2022 period. The data analysis technique uses the eviews 12 analysis method. The results of this research  show that purchases  and receivables do not affect the company's profit, while cash flow affects the company's profit.